Pid Controlled Line Follower Robot Design on Indoor 3D Networks - Oguz KOSE; Ismail Rakip KARAS (IAES Indonesia Section, 2014)
Robots are commonly used and developed for different purposes in various areas such as research, educational, commercial, and industrial fields, also in emergency situations and space missions in today’s modern world. Robots are the machines that increasingly gain the importance with each passing day by the development of micro-electronics and micro-mechanics industry. To define a machine as a robot, it needs to have the sensors to check its environment; the mechanisms to evaluate the information received from these sensors and to transfer to the processing units.In this study, an intelligent controlled line follower robot was developed. Proportional-integral-derivative (PID) method was used for controlling. According to the information from the sensors, the method applied to the engines as Pulse Width Modulation (PWM). Online Fez Panda II embedded system board was used as the control element. This board has a 2-bit ARM 7 (Acorn RISC Machine) processor and it is suitable to .Net Micro Framework Technology. The system software was written with C# programming language in Visual Studio 2010 platform.The robot was tested on 3D indoor network, and has potential to be used for evacuation process on extraordinary sitautions in buildings. Another usage areas of this robot are factories and production lines. 3D network analyses and navigation applications could also be performed using the lines on the ground of this kind of environment.